A Third-Generation Adaptive Statistical Iterative Reconstruction for Contrast-Enhanced 4-Dimensional Dual-Energy Computed Tomography for Pancreatic Cancer. Issue 1 (January 2021) - Ohira, Shingo; Kanayama, Naoyuki; Wada, Kentaro; Washio, Hayate; Karino, Tsukasa; Ueda, Yoshihiro; Inui, Shoki; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Abstract : Objectives: The objective of this study was to assess the objective and subjective qualities of the contrast-enhanced 4-dimensional dual-energy computed tomography using adaptive statistical iterative reconstruction (ASiR) and ASiR-V. Methods: The virtual monochromatic images at 60 keV were reconstructed using filtered back projection, ASiR, and ASiR-V (10%–100%) for 14 patients with pancreatic cancer. The contrast-to-noise ratio (CNR) was calculated, and the subjective measurements were compared based on a 5-point score scale. Results: The ASiR-V yielded a significantly higher CNR than ASiR ( P < 0.05). The subjective image quality (peak) was significantly improved ( P < 0.01) with ASiR (50%) (3.8, 3.5, and 4.0; overall image quality, tumor delineation, and noise, respectively) and with ASiR-V (50%) (3.9, 3.5, and 4.2, respectively) compared with the filtered back projection (3.2, 3.2, and 3.0, respectively). Conclusions: The ASiR-V yielded higher CNR than ASiR and provided the highest subjective scores regarding the overall image quality.